Supporting Common Core Instruction With Literacy Design Collaborative - Joan Herman; Scott Epstein; Seth Leon (SAGE Publishing, 2016)
The article examines the results of two quasi-experimental studies of the implementation and impact of the Literacy Design Collaborative (LDC), an intervention designed to support secondary teachers' transition to Common Core State Standards in English language arts. The first study examines LDC implementation by eighth-grade social studies and science teachers in districts across Kentucky; the second study is set in sixth-grade advanced reading classes in a large urban district in Florida. Based on teacher surveys, logs, and analysis of classroom artifacts, the LDC was implemented with reasonable fidelity across both studies. Based on available assessment scores, results show statistically significant positive effects in Kentucky for reading but no corollary effect in Florida. There were no significant differences in writing scores in either site. The conclusion shares hypotheses that may explain the differences in results and reflects on implications for evidence-based practice.